Utilization of Digital Information Boards as Media Information in Rural Areas: Pemanfaatan Papan Informasi Digital Sebagai Media Informasi di Wilayah Perdesaan - Fadli, Ari; Purnomo, Widhiatmoko Herry; Sugiyanto, Gito; Aliim, Muhammad Syaiful (Yayasan Ahmar Cendekia Indonesia, 2020)
Information is one of the most important human needs. The term information is often understood as an aid in decision making process needed for the decision makers. Subdistrict offices, village offices, or other government offices are required to be able to provide various information needed by the community. The presence of signage as a medium for delivering information at the subdistrict offices, village offices or other government offices is still considered an important medium in fulfilling information according to the community needs. Digital Signage is one of the electronic media which is currently often used in fulfilling the required information. Digital signage is a one-way digital information service. This community service activity was carried out with the aim of building a digital signage by using an Android TV device. The use of this Android TV-based digital signage can assist village officials in compiling digital-based information, where its use is also considered as easy as using an Android-based mobile device. Abstrak Informasi merupakan kebutuhan yang sangat penting, dasar dalam pengambilan keputusan salah satunya adalah bersumber dari informasi tersebut. Kantor Kelurahan, kantor desa ataupun kantor pemerintahan lain syarat akan informasi yang dibutuhkan oleh masyarakat umum. Kehadiran papan pengumuman sebagai media penyampai informasi di Kantor Kelurahan, kantor desa ataupun kantor pemerintahan lain hingga saat ini tetap menjadi hal penting yang dapat digunakan untuk memenuhi kebutuhan masyarakat akan informasi. Papan Informasi digital (Digital Signage) merupakan salah satu media elektronik yang saat ini sering digunakan untuk memberikan informasi yang dibutuhkan. Papan pengumuman digital (digital signage) adalah Sebuah layanan informasi berbasis digital satu arah. Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah membangun papan informasi digital dengan menggunakan menggunakan perangkat android tv. Hadirnya Papan informasi digital berbasis Android TV ini memberikan kemudahan bagi perangkat desa dalam membuat informasi berbasis digital dikarenakan kemudahan penggunaannya yang sama dengan perangkat handphone berbasis android.